Co-localization of proteins with defined sequential order and controlled stoichiometric ratio on magnetic nanoparticles. Issue 13 (20th March 2017) - Yue, Yi; Lu, Yang-Yang; Li, Mei; Zhang, Zi-Jian; Tan, Tian-Wei; Fan, Li-Hai
Abstract : Here we reported a method for controlled co-immobilization of multiple proteins on magnetic nanoparticles by using cohesin–dockerin and His tag-nickel(ii ) interactions. Abstract : Co-immobilization of enzymes used in cascade reactions is important for improving the overall catalytic efficiency. In this work, we employed scaffoldins as a bridge and succeeded in a highly-ordered co-localization of multiple proteins on magnetic nanoparticles with a loading capacity of ∼0.831 μmol g −1 supports.